An Analysis of Pedagogical and Barriers in Entrepreneurship Education in Secondary Schools: A Global Perspective - Furqanisah; Johan, Riche Cynthia (Universitas Islam Negeri Raden Intan Lampung, 2026)
Entrepreneurship education at the secondary school level plays a crucial role in developing young people's entrepreneurial skills and attitudes. However, implementing it still faces various conceptual and structural challenges. This study uses a systematic literature review with the PRISMA approach to examine the forms of implementation, pedagogical practices, and barriers in entrepreneurship education, focusing on Scopus-indexed publications from 2000 to 2025. The findings reveal five primary implementation forms: cross-disciplinary activities (the most prevalent), extracurricular programs, workshops, external partnerships, and mandatory subjects. Commonly recommended pedagogical practices include student-centered active learning, experiential learning, and problem-based projects. The main barriers consist of weaknesses in curriculum organization, limited resources, differences in teacher interpretations, low educator competence, and unsupportive school cultures. These findings underscore the need to strengthen the policy framework for entrepreneurship education at the school level, enhance teacher capacity, and provide continuous professional development, as well as adequate institutional support and resources, to ensure the effectiveness and sustainability of entrepreneurship education implementation in secondary schools.